Pengembangan Media Baamboozle dengan Model Hannafin-Peck untuk Meningkatkan Motivasi Belajar Pendidikan Agama Islam - Kamilia, Dina; Sa'diyah, Halimatus; Mutammimah, Darun; Mubarok, A. Khuzainol; Juhairiyah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to develop Baamboozle as an interactive, technology-based learning medium to enhance students’ learning motivation in Islamic Education, particularly in understanding multicultural concepts from an Islamic perspective. The Research and Development (R&D) method was applied using the Hannafin and Peck model, which consists of three systematic stages: needs analysis, design, and development–implementation. The development process included expert validation, media refinement, and user testing involving PGMI Class A students at UIN Madura. The findings indicate that the Baamboozle media meets the feasibility criteria based on expert evaluations and student responses. Material experts assessed the product at 86%, linguists at 84%, and media experts at 89%, all categorized as feasible. Meanwhile, student assessments yielded 72%, falling into the sufficiently feasible category. These results demonstrate that Baamboozle is not only appropriate for instructional use but also has the potential to strengthen students’ learning motivation through interactive and engaging quiz-based activities. Overall, this research confirms that the systematic development of digital learning media using the Hannafin and Peck model can effectively support Islamic Education learning, particularly in topics requiring conceptual understanding and active participation.